Music entrepreneurship - Dumbreck, Allan; McPherson, Gayle, 1968- (Bloomsbury Methuen Drama, 2016)
The music industries hinge on entrepreneurship. The recent, rapid convergence of media and the parallel ongoing evolution of music businesses have again seen the focus shift to independent companies and individual entrepreneurs. Opportunities tend not to be advertised in professional music and practically everyone begins on their own: forming a band, starting a record label, running events, or building a website. But it's not an easy territory to navigate or get a handle on. Music Entrepreneurship features an analysis of the changing landscape of the music industries and the value of the entrepreneur within them through a series of focused chapters and case studies. Alongside contributions from key academics across the globe, expert contributors from across the industry highlight successful entrepreneurs and offers practical help to the reader trying to navigate the business. Sectors examined include: The value of the music industries Recorded music Live events Branding in music Artist management Digital distribution.
Keywords: Music trade.; Music -- Economic aspects.; Entrepreneurship.; Entrepreneurship; Musique -- Industrie.; Musique -- Aspect économique.; Entrepreneuriat.; entrepreneurs.; MUSIC -- Genres & Styles -- Classical.; MUSIC -- Reference.; Music -- Economic aspects; Music trade